Contrast induced nephropathy in interventional cardiology; identification of high-risk patients and its prevention. (11th May 2022) - Shuka, N; Kristo, A; Gishto, T; Simoni, L; Hasimi, E; Shirka, E; Siqeca, M; Lazaj, J; Refatllari, I; Xhafaj, M; Seiti, J; Mijo, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: CIN is a serious and potentially preventable complication of coronary angiography and/or percutaneous coronary interventions (PCI). The definition of CIN, its incidence and risk factors and therapeutic interventions are not well established . Purpose: To study incidence and risk factors of CIN in patients undergoing coronary angiography and/or PCI, to investigate high-risk patients with CIN and to evaluate its preventive therapies (Hydration an Acetylcysteine). Method: This was a prospective trial, in one center with patients undergoing coronary angiography and/or PCI, during 2010-2014. The renal function was evaluated through serum Creatinine (Cr) and GFR (Cockcroft –Gault formula ). CIN was defined as an increase in Creatinine by 25% and/or by 0.5 mg/dL at 48/72 h after the index procedures. Patients with CIN were considered high-risk when Creatinine increased more than 50% and/or by 2 mg/dL, or needing dialysis. We evaluated the major risk factors for CIN such as: Preexisting Renal Lesion (PRL), Age≥65 years, Heart Failure (HF), Diabetes Mellitus (DM), Anemia (Hb < 12 g/dL) and the Quantity of Contrast used. We evaluated the role of hydration with intravenous saline and acetylcysteine (ACC) in the prevention of CIN. Results: Out of the 1231 patients enrolled, 804 patients fulfilled the inclusion criteria. The incidence of CIN resulted 14.4%, higher in the group of patients with risk factors for CIN (15.3%) versus without risk factors (9.1%); p=0.05. Risk factors HF (OD: 4.63; CI95%: 2.10-10.05, p<0.001), PRL (OD: 1.57; CI95%: 1.02-2.41, p=0.039) and Age ≥ 65 years (OD: 1.82; CI95%: 1.37-3.73, p=0.038 ) resulted independent risk factors, for CIN whereas Anemia (p=0.171), DM (p=0.502) and the Quantity of contrast used (p=0.479) did not result independent risk factors. Creatinine at 24 hours after the procedure resulted a predictive factor for the development of CIN. (sensitivity 64.7%, specificity 91.7%, positive predictive value 63.5%, negative predictive value 92.1% ). Creatinine > 1.5 mg/dL before the procedure resulted an independent risk factor for CIN, with a higher specificity than eGFR < 60 ml/min. The incidence of patients with CIN at high risk was 3.9% and HF resulted the only independent risk factor in this subgroup of patients (OD:4.49, CI 95%: 2.03-9.95). Intravenous hydration with saline resulted efficient in the prevention of the development of CIN (p=0.029), whereas ACC did not (p=0.485). Conclusions: The frequency of CIN is higher in the group with risk factors. The HF, PRL, Age≥ 65 years resulted as independent risk factors for, and intravenous hydration with saline was a simple and efficient method for the prevention of CIN. Although our definition of CIN is widely used, the need for a universal definition for CIN is a contemporary need.